Analysis of Maternal and Child Health Indicators in an Area at Paraná State, Brazil - Emiliana Cristina Melo; Ana Beatriz Guedes Ribeiro; Rosana Rosseto de Oliveira; Robsmeire Calvo Melo Zurita; Thais Aidar de Freitas Mathias (Hindawi Limited, 2013)
The aim of this study was to analyze maternal and child health indicators and infant mortality rate (IMR) at the cities located at the 18th Health Division (HD) in Parana State, Brazil. In this ecological study we analyzed all live births and infant deaths which occurred from 2000 to 2009 at the 18th HD, collecting data from the Mortality Information Database and the Live Births Information Database. The variables assessed were grouped into maternal, pregnancy and delivery, and neonatal variables. The analysis was conducted using the mean percentage of each variable and the IMR calculated for both periods: from 2000 to 2004 and from 2005 to 2009. The IMR was reduced considerably, following Brazil's and Paraná State's trend. Maternal indicators went down regarding the mean percentage of teenage mothers and low education, whereas they went up regarding mother with 35 years old or older and mothers without a partner. Pregnancy indicators showed increased prematurity and cesarean birth. Neonatal indicators raised in black/brown skin color and low birth weights percentages. This study provides a better understanding of maternal and child health in the cities located at the 18th HD, supplying grounds to plan actions regarding the real needs of each specific city.